The Relationship between Work Motivation and Nurse Performance at RSU Royal Prima Medan In 2023 - Utami, Sherlinda Putri; Ginting, Chirmis Novalinda; Chiuman, Linda (Fakultas Kedokteran Universitas Malikussaleh, 2024)
Motivation is an internal impulse that determines what a person does and the enthusiasm for doing it. Motivation itself consists of two types, namely internal and external motivation, internal motivation subvariables which have the strongest relationship with nurse performance in the form of recognition, achievement and development while external motivation subvariables which have the strongest relationship with nurse performance are working conditions, organizational policies, salary/ wages.. Objective: The aim of this research is to determine the relationship between work motivation and nurse performance at RSU Royal Prima Medan in 2023. The type of research used in this research is quantitative research with a cross-sectional design. The population used in this research were 349 nurses at RSU Royal Prima Medan in 2023. Sampling used the Slovin formula with a total sample of 78 samples. The research data used is primary data with the research instrument used, namely a questionnaire. Data analysis in this study used univariate, bivariate and multivariate analysis. The results of the analysis show that the majority of respondents' internal motivation in this study is high and there is a relationship between internal motivation and nurse performance at RSU Royal Prima Medan in 2023 p-value of 0.000 < 0.05. The majority of respondents' external motivation in this study was high and there was a relationship between external motivation and nurse performance at RSU Royal Prima Medan in 2023 p-value of 0.000 < 0.05. The independent variable that has the most influence on the dependent variable is the external motivation variable. There is a relationship between external motivation and the performance of nurses at RSU Royal Prima Medan.